A comprehensive study on highly active pentiptycenyl-substituted bis(imino)pyridyl iron(II) mediated ethylene polymerization. (5th April 2020) - Zhang, Yuxing; Wang, Chaoqun; Jian, Zhongbao
Graphical abstract: Highlights: Comparison on pentiptycenyl and dibenzhydryl bis(imino)pyridyl iron(II) catalysts. Too large steric bulk in bis(imino)pyridyl iron catalysts is not the best choice. Temperature, time, pressure, alkyl aluminum reagents affect ethylene polymerization. Chain transfer to monomer is a major process to generate vinyl oligoethylenes. A tandem catalysis with Friedel-Crafts addition of vinyl oligoethylene is observed. Abstract: Ligand steric bulk is of paramount importance in late transition-metal mediated olefin polymerization. In this contribution, we designed and prepared two structurally similar bis(imino)pyridyl iron(II) complexes bearing 2, 6-bis(dibenzhydryl)phenyl N -aryl moiety (Ph-Fe ) and pentiptycenyl N -aryl moiety (Ipty-Fe ) to reveal the huge effect of steric bulk on ethylene polymerization. Two iron(II) complexes were confirmed by NMR spectroscopy, mass spectroscopy, elemental analysis, and vital X-ray diffraction analysis, which indicates that Ph-Fe has a larger buried volume around the metal center than Ipty-Fe (%Vbur : 55.5 vs. 52.7). As a result, in the presence of Al reagent, Ph-Fe showed extremely low activity for ethylene polymerization, but Ipty-Fe with a less steric blockage exhibited much higher (two orders of magnitude) activity (up to 25, 500 kg mol −1 h −1 ). Reaction temperature, time, pressure, type and amount of Al reagents were comprehensively studied to evaluate and compare these two iron(II) complexes. More interestingly, chain-end-functionalization of these obtained polyethylenes bearing vinylic end-groups could be achieved in situ by the Friedel-Crafts addition to aromatic toluene as the reaction solvent at elevated temperature or high ratio of [Al]/[Fe].